A monoclonal macroglobulin with antinuclear activity. Issue 5 (May 1979) - Intrator, L; Andre, C; Chenal, C; Sultan, C
Abstract : Serum containing a monoclonal IgM protein from a patient with Waldenstroms' macroglobulinaemia gave intense immunofluorescent staining of kidney nuclei. The Fab mu fragments of this immunoglobulin were obtained. The IgM and Fab fragments reacted in vitro with kidney nuclei using unfixed cryostat sections of rat or mouse kidney. After treatment of the patient with chemotherapy, the monoclonal IgM disappeared, and no more antinuclear activity could be detected in the serum. The results strongly suggest that this IgM protein had antinuclear activity.